Adiposity biomarkers and lipid profile in Costa Rican school children in San Juan de La Union district, Cartago province - Aguirre, Raquel Arriola (2020)
Introduction: Childhood obesity is a public health problem in the world, being a predisposing condition for the development of excess weight in adulthood and consequently of chronic diseases such as cardiovascular disease, diabetes, metabolic syndrome, among others, hence the importance of its detection in early stages of life for prevention and / or treatment. Alterations in plasma concentrations of leptin and adiponectin in childhood are the reason for the metabolic alterations that may occur in this population such as insulin resistance, high blood sugar levels and altered lipid profile. The imbalance of these adipokines is the metabolic consequence of excess adipose tissue in the individual. Therefore, the objective of the present study was to analyze the lipid profile and biomarkers of adiposity, in order to establish the prevalence of dyslipidemias and risk of atherogenicity in school children in the Tres Ríos district, La Unión canton, Cartago province. Methodology: The serum concentration of leptin, adiponectin, insulin and lipids was determined from a group of 108 schoolchildren from the canton of La Unión, Cartago, Costa Rica, aged between 6 and 10 years, to whom the anthropometric evaluation and duplicate determination of biomarkers. Results: Plasma concentrations of total cholesterol and triglycerides were outside the normal range in the study population. Excess weight shows a significant and positive relationship with plasma concentrations of leptin and insulin. Conditions such as age and sex did not affect the behavior of the indicators studied. Conclusions: Total cholesterol, triglycerides, leptin, and insulin could be metabolic indicators for monitoring the risk of chronic diseases in pediatric populations.